Türkiye’ de kamu bankaları ve bankacılık sektöründeki yeri - Ege, Barış (My University, 2002)
Kamu işletmeciliği hemen bütün ülkelerde aynı gerekçelerle başlamıştır. Türkiye'nin gerekçelerinin daha da güçlü olduğu, Cumhuriyetin ilk dönemlerinde devlet eliyle sanayileşmeye karar verilmesinde, bazı zorunluluklar ve koşulların etkisi bulunduğu kanısı hayli yaygındır. Şöyle ki; Cumhuriyetin kurulmasından sonra ekonomik gelişmeyi hızlandırabilmek için devlet tarafından bir çok alanda işletmeler kurulmuştur. Özel sektörün sahip olduğu kaynakların yeni kurulan Cumhuriyetin sosyal ve ekonomik hedeflerini gerçekleştirmede yetersiz olması yatırımların büyük bir çoğunluğunun devlet tarafından yapılmasını zorunlu kılmıştır. Buna paralel olarak çeşitli sektörlerde finansman ihtiyacının karşılanabilmesi için uzman bankalar kurulmuştur. Etibank, Sümerbank, İller Bankası ve Halk Bankası farklı sektörleri ve hizmetleri finansal yönden desteklemek için bu dönemde kurulmuştur. Kamu kuruluşlarının ve bankalarının kurulmasında diğer bir neden ise milli sanayiyi, bankaları ve beraberinde ulusal sermaye birikimini oluşturmaktır. Diğer yandan, oluşturulan kamu kuruluşları ve bankalar ile piyasalar kontrol edilerek ve yönlendirilerek ekonomik ve sosyal kalkınma gerçekleştirilmeye çalışılmıştır. Kurumsal olarak kamu bankaları ve bankaların kurulmasındaki temel amaç uzun vadede ekonomide artı değer yaratmak ve bunları tekrar yatırımlara dönüştürerek toplumun kalkınmasını gerçekleştirmek olarak belirlenmiştir. Ayrıca şunu da ifade etmek gerekir ki, devlet işletmeciliğinin Cumhuriyetin ilk yıllarında başarılı örnekler verdiği yadsınamaz bir gerçektir. Ancak 1970'li yıllardan itibaren kamu kuruluşları ekonomik dengelerin oluşturulmasında her geçen gün toplum için ekonomik ve sosyal açıdan yük getirmiştir. Söz konusu yıllarda devletin artan fonksiyonları ve genişleyen boyutları ve bu durumun ortaya çıkardığı sorunlara Keynesyen iktisat politikasının çözüm önerememesi üzerine, temelde Klasik İktisat Teorisi ilkelerine dayalı, ancak onu bazı yönlerden eleştiren ve yeniden yorumlayan başka iktisat politikası yaklaşımları gündeme gelmiştir. Burada şunu da ifade etmek gerekir ki, Türkiye'de özelleştirme tartışmalarının yoğunlaştığı alanlardan birisi de kamu sermayeli bankalardır. Özellikle bankacılık sektöründe rekabetin, verimliliğin ve etkin kaynak kullanımının sağlanması, bankacılık sektörü-siyaset ilişkisinin ortadan kaldırılması ve kamu bankalarına çağdaş/ dinamik bir yapı kazandırılması gibi hedefler özelleştirme uygulamalarının kamu sermayeli bankalar üzerinde yoğunlaşmasına sebebiyet vermiştir. Gerçekten de, Türk bankacılık sektörü incelendiğinde toplam mevduatların büyük bir bölümünün (yaklaşık %40) kamusal sermayeli bankaların elinde olduğu görülmekte, bu durum ise bankacılık sektöründe yaratılan kaynakların büyük bir bölümünün kamu kesimince yönlendirildiği anlamına gelmektedir. Sektörde yaratılan fonların kamu kesimine akması ise kaynak dengesini bozduğu gibi sektördeki rekabeti olumsuz yönde etkilemektedir. Genelde özel görevler için kurulan, ancak daha sonra ticaret bankacılığına yönelen kamu bankalarının sermaye yapısı rekabetçi olmalarını engelleyen en önemli nedenlerin baışında gelmektedir. Çünkü, kamu bankalarının finansal açıdan ülke hazinesine bağlı olması, sık sık politik müdahalelerle karşılaşmaları etkinliklerini azaltarak, finansal yapılarını bozmakta, sürekli zarar eden kamu bankalarını sermaye sorunu ile karşı karşıya bırakmaktadır. Öte yandan, Türkiye'de kamu bankalarının politik bir güç ve baskı aracı olarak kullanıldığı, hükümetlerin kamu bankalarını birer istihdam alanı ve ucuz kredi aracı olarak gördükleri ileri sürülmekte ve bu durumun, Türk bankacılık sektörünün en önemli sorunu olduğu iddia edilmektedir. Ayrıca, Türkiye'de bankacılık sektörü toplam aktifleri içinde devletin sahip olduğu/ yönettiği bankaların aktiflerinin önemli bir yer tuttuğu ve bu bankaların bankacılık ilke ve kuralları yerine, politik öncelikler çerçevesinde yönetildiği, bu durum ise bankacılıkta rekabeti ve bankacılık sektörünün yapısını olumsuz yönde etkilediği ve kamu bankalarının kullandırdığı kredileri politik önceliklere göre tahsis etmekte olduğu da önemli iddialar arasındadır. Bu çalışmada, Türkiye'de ki kamu sermayeli ticaret bankalarının etkinlik ve verimlilik tartışmalarına ışık tutabilmek amacıyla kamu ve özel sermayeli bankalar çeşitli etkinlik/ verimlilik ve diğer performans ölçüm oranları ile karşılaştırılmaktadır. Şöyle ki; önce, aktif büyüklüğü ölçütü esas alınarak Ziraat Bankası, Emlak Bankası, Halk Bankası ve Vakıflar Bankası olmak üzere 4 kamu sermayeli ticari banka ile Yapı ve Kredi Bankası, Akbank, İş Bankası ve Garanti Bankası olmak üzere 4 de özel sermayeli ticari banka seçilmiştir. Daha sonra ise söz konusu bankaların 1994-2000 dönemini kapsayan ve Türkiye Bankalar Birliği'nce yayınlanan gelir tablosu ve bilançoları kullanılarak, etkinlik, verimlilik ve diğer performans ölçüm oranları hesaplanmakta, böylece her iki banka grubu karşılaştırmalı bir şekilde ortaya konulmaktadır. Böylece, kamu bankalarının verimsiz olduğu yönündeki yaygın kanaat 1994-2000 dönemi verileri kullanılarak test edilmektedir. Üç bölümden oluşan bu çalışmanın birinci bölümünde ticari bankacılığa ilişkin teorik yaklaşımlar üzerinde durulmaktadır. İkinci bölümde ise; Türkiye'de ticari banka sayısı ile bu bankaların şube ve personel sayılarının yıllara göre gösterdiği gelişmeler kamu ve özel sermayeli banka grupları açısından irdelenmiştir. Daha sonra Türk Ticari Bankacılık sektöründe toplam aktifler, toplam mevduatlar ve toplam kredilerin yıllara göre kamu ve özel sermayeli banka grupları arasındaki dağılımı üzerinde, toplam aktif büyüklüğü ölçütü kullanılarak 4 kamu (Ziraat Bankası, Emlak Bankası, Halk Bankası ve Vakıflar Bankası) ve 4 de özel (Yapı ve Kredi Bankası, Akbank, İş Bankası ve Garanti Bankası) sermayeli banka olmak üzere toplam 8 banka seçilmiştir. Bu aşamadan sonra ise söz konusu bankaların Türkiye Bankalar Birliği'nce yayınlanan 1994-2000 dönemi bilançoları kullanılarak etkinlik, verimlilik ve diğer bankacılık performans ölçüm oranları her iki banka grubu için ayrı ayrı hesaplanmış ve bu oranlar vasıtasıyla kamu ve özel sermayeli banka gruplarının karşılaştırılması üzerinde durulmuştur. Üçüncü ve son bölümde ise; bankacılık sektörünün yeniden yapılandırma evesinde kamu bankalarının yeniden yapılandırılması hususunda sağlanan gelişmeler üzerinde durulmuştur.

Public administration has started because of some reasons in all states. In general opinion, The Turkish Republic's reasons have been more serious. Industrialization by the help of the Government has been a necessity during the early periods of the new Turkish Republic. After the foundation of the new Republic, lots of public administrations have been founded by the Government to speed up economic development. Assets of the private sector has been insufficient to realize the new Republic's social and economic targets to materialization of large scale investments by the Government. So, special banks have been founded by the Government to finance different sectors. Etibank, Sümerbank, İller Bankası and Halk Bankası have been founded in this period to support financially that different sectors. The other reason for the foundation of public administrations and banks has been realization of capital accumulation and support national industry. Social and economic development has been speeded up by the public organizations and banks. The main target for the foundation of the state banks has been to create public value, to increase savings and to use that savings for investments. In that system, public administrations and banks has resulted successful investments during the early years of the new Republic. But after 1970's, public administrations has caused some problems for economic balances. The role of the Government in the economic life has expanded. The public administrations has emerged as organizations that aren't profitable and efficient. When the Turkish banking sector is examined, we see that; Nearly half of the total deposits (nearly 40 %) is held in state banks. It means that, nearly half of the total savings in the Turkish banking sector is managed by the state banks. Management of the funds in the banking sector causes some problems and negative effects about fund-balances and competition in banking sector and economy. Capital forms of the state banks that have been founded some special targets, than started to manage with commercial banking are the main reasons that cause an incompetitive forms in the banking sector. By the financial way, state banks are dependent on Treasury and so state banks are often exposed to political interventions. That some political interventions caused problems on state banks' financial constructions and profitabilities. State banks have been used as political power and as a employment boxes for their supporters and voters and as a source of cheap loans for their supporters by the Governments. State banks' total assets has a large percentage in the total assets of the Turkish banking sector and instead of working in rules and style for profit and efficiency, are managed with political precedences. In this work, state and private sector banks has been compareted with several effectiveness, productivity and performance ratios to explain commercial banks' effectiveness and productivity in Turkish banking sector. First of all, 4 state banks that are T.C. Ziraat Bankası A.Ş., T.C. Emlak Bankası A.Ş., T.C. Vakıflar Bankası A.Ş. and T.C. Halk Bankası A.Ş. have been selected to represent state banking sector in Turkey and 4 private sector banks that are Türkiye Yapı ve Kredi Bankası, Akbank, Türkiye Garanti Bankası and Türkiye İş Bankası A.Ş. have been selected to represent private sector banking in the Turkish banking sector according to their percentage of assets in the Turkish banking sector. Then, their effectiveness, productivity and performance ratios have accounted by the help of 1994-2000 balance sheets and income statements that has been published by Türkiye Bankalar Birliği. In this way, that mentioned ratios have been counted for the 2 banking groups to compare and test their performance and profitability for the period of 1994-2000 years. The work is composed of 3 Chapters. In the first Chapter, theoretical information is explained about commercial banking. In the second Chapter, number of commercial banks, number of banks' branches and personnel have been explained for the private and state banks between the period of 1994-2000 years. Then, 4 state banks that are T.C. Ziraat Bankası A.Ş., T.C. Emlak Bankası A.Ş., T.C. Vakıflar Bankası A.Ş. and T.C. Halk Bankası A.Ş. have been selected to represent state banking sector in Turkey and 4 private sector banks that are Türkiye Yapı ve Kredi Bankası, Akbank, Türkiye Garanti Bankası and Türkiye İş Bankası A.Ş. have been selected to represent private sector banking in the Turkish banking sector according to their percentage of assets in the Turkish banking sector to account and compare their profitability, effectiveness and efficiency by the help of 1994-2000 balance sheets and income statements that have been published by Türkiye Bankalar Birliği. In the third and last Chapter, developments that have been realized about reinstruction program of banking sector and state banks' reinstructions have been explained. When the total amount of deposits and the total amount of loans are examined, we see that results: The private sector banks that hold 57% of the total amount of deposits, give 67% of the total amount of loans, but the state banks that hold 41% of the total amount of deposits give 30% of the total amount of loans in the Turkish banking sector. So, the ratio of the total loans to total deposits for the state banks is nearly 30%, while the same ratio is 60% for the private banks. These ratios show that state banks can hold more deposits than private banks because of the Government's full guaranty on deposits, higher interest rates, lots of branches and public organizations' deposits that are held in the state banks. So, the state banks hold 41% of the total amount of deposits, but give only 30% of the total amount of the total loans in the sector. This state explicit that the state banks use the deposits that are deposited to the state banks any different areas apart from giving loans to markets. In spite of, a part of non-performing loans are being hidden in the balance sheets of the state banks for not being obligatory for non-performing loans reserves; the loans that have been given to the Treasury and non-performing, have been written duty losses in the balance sheets, the ratio of non-performing loans to the total loans for the state banks is 9% (this ratio is 18% for T.C. Ziraat Bankası A.Ş. and 29% for T.C. Emlak Bankası A.Ş.), while the same ratio is 1% for the selected private banks. So, we can say that, state banks have been often exposed to political interventions during loans-giving duration. When the income statements of the state banks and private sector banks are examined we see that: The ratio of the interest-income to the total income is about 80% for the state banks, while the same ratio is under this percentage for the selected private sector banks. But, the ratio of the operations income (except interest-income) to the total income for the state banks is quietly under private sector banks'. When the ratio of net profits to the total assets, the ratio of net profit to the capital, the ratio of net profit to the total deposits, the ratio of net profit to the total loans are examined we see that the mentioned ratios for the state banks are lower than the private banks' and negative values for T.C. Emlak Bankası A.Ş. especially in last years. When the ratio of net interest-income to the total assets, the ratio of net interest-income to the capital, the ratio of net interest-income to the total deposits, the ratio of net interest-income to the total loans are examined we see that the mentioned ratios for the state banks are lower than the private banks' and negative values for T.C. Emlak Bankası A.Ş. especially in last years. So, it's impossible to say about profit for the state banks. The results of the analyses about state banks' place in the Turkish banking sector shows that profitability, effectiveness and efficiency of the state banks are lower than selected private sector banks'.
Keywords: Banka ve bankacılık; Bankalar Ve Bankacılık Türkiye; Ekonomi; Finansman ekonomisi